EFL STUDENTS’ READING STRATEGIES AND READING PROBLEMS WHILE WORKING ON READING TEST - Sarina Jawahit Amir (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The study aimed to investigate reading strategies implemented by EFL students and reading problems faced by EFL students while working on reading test. The research design of this study is a descriptive qualitative study in the form of interview. There were 22 freshmen of English education department participate in this study and they divided into the highest and lowest achiever categories by using reading test consisting of 30 multiple choice questions. Besides, the interview questions used to know the reading strategies used by high achiever students and the reading problems encountered by low achiever students in reading test. The result of the study showed that the high achiever students used to apply strategies while working on reading test. The other result of this study showed that he low achiever students faced some problems while working on reading test. It was proved that there were reading strategies used by high achiever students in reading test and reading problems faced by students while reading test. Keywords: Reading strategies, reading problems, reading test